Empowering Women for Conflict Resolution and Management (Unilorin Journal of Lifelong Education, 2025)
Conflict is inevitable in both developed and developing nations as well as at homes, places of worship and communities. It is therefore, important for women to be empowered for effective participation in conflict resolution in order to bring about enduring and sustainable peace. According to Tearfund (2014), an organisation that is committed to peace building in situations of conflicts by equipping movements and people, is of the opinion that people including women should work together to prevent and respond to conflicts. This can be achieved by examining the root causes of conflicts in order to restore broken relationships and respond promptly to crisis. This implies that efforts at resolving and managing conflict must not be exclusive but inclusive involving cooperation, collaboration and understanding of the conflicting situation. Women must, therefore, be empowered to develop objective and constructive views to political and social relationships across ethnic, religion, class, home, national and racial boundaries; the purpose of which is to resolve injustice across board, in possibly non-violent ways and transform and address the conflicting situations. When women are involved in conflict resolutions, there is not only peace in communities, but also endurable peace and self-sustaining development.